Geographical and Literary Lineage In Te Works of Salman Rushdie: Exploring the Global and Local Dimensions of Salman Rushdie's Works (Journal of Advances and Scholarly Researches in Allied Education, 2012)
Michael J. Sandel in his book entitled Democracy'sDiscontent: America in Search of a Public Philosophy writes: The global media and markets that shape our lives beckonus to a world beyond boundaries and belonging. But the civic resources we needto in the places and stories, memories and meanings, incidents and identities,which situate us in the world and give our lives their moral particularity.(349) This does not rule out global systems but posits anetwork of the global, the national and the local. In it, while we remainencumbered in our local communities we also recognize other loyalties, andnegotiate our way intelligently between them. To quote Sandel again,Self-government today requires a politics that plays itself out in amultiplicity of settings, from neighborhoods to nations to the world as a whole... The civic virtue distinctive to our time is the capacity to negotiate ourway among the sometimes overlapping, sometimes conflicting obligations thatclaim us, and to live with the tension to which multiple loyalties give rise.(350) Salman Rushdie could be best described as having multipleloyalties, even multiple belongings - to India, to Britain, to the world -rather than as having none at all. Pico Iyer, a dislocated, displaced, andderacinated man, rightly salutes his fellows when he describes Rushdie as 'aconnoisseur of dislocation' (148), and Michael Ondaatje as coming from a familyof' deracinated cosmopolitans' (136).